Et nytforkyndelsessprog: En studie i F.C. Krarups praktiske teologi - Foss, Poul Juul (Kirkehistoriske Samlinger, 1993)
F.C. Krarup (1852-1931), doctor of theology and for many years vicar in Sorø of Zealand, is generally considered the foremost representative of liberal theology in Denmark. His viewpoint have been considered rather moderate. Against this view, the article presents Krarup as a radical theologian. Underscoring this claim, an analysis of his understanding of the form, content and task of the Christian message is presented. In this connection, Krarups strongly Kant-influenced epistemology is discussed and his Schleiermacher-influenced religious psychology, as well as his relations to Danish philosophers (primarily Harald Høffding), are emphasized. A central aspect of the article is an interpretation of Krarup’s use of linguistic symbols and pictures as mediators of the message of transcendence to immanence. Given his philosophical starting -point, Krarup rejects all metaphysics, but argues that we through the picture of Jesus of Nazareth we come into contact with the highest values of being, which are called God. The belief in God means trusting the best in ourselves.